Emerging Mechanisms of Growth and Patterning Regulation by Dachsous and Fat Protocadherins - Gridnev, Artem; Misra, Jyoti R. (Frontiers in Cell and Developmental Biology, 2022)
Dachsous (Ds) and Fat are evolutionarily conserved cell adhesion molecules that play a critical role in development of multiple organ systems, where they coordinate tissue growth and morphogenesis. Much of our understanding of Ds-Fat signaling pathway comes from studies in Drosophila, where they initiate a signaling pathway that regulate growth by influencing Hippo signaling and morphogenesis by regulating Planar Cell Polarity (PCP). In this review, we discuss recent advances in our understanding of the mechanisms by which Ds-Fat signaling pathway regulates these critical developmental processes. Further, we discuss the progress in our understanding about how they function in mammals.